2018
DOI: 10.1002/jclp.22682
|View full text |Cite
|
Sign up to set email alerts
|

Adapting psychotherapy to patient reactance level: A meta‐analytic review

Abstract: Resistance and its extreme variation, reactance, are uniformly observed across varieties of psychotherapy.Social psychologists note that reactant individuals prove to be less so when offered a receptive and nondirective environment. We provide definitions of reactance, review its frequent measures, and offer a clinical example. A meta-analysis of 13 controlled studies (1,208 patients) examined the degree to which treatment outcomes are enhanced when therapists offer less directive treatments to high-reactance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 22 publications
1
27
0
3
Order By: Relevance
“…La resistencia del paciente con respecto al cambio es uno de los principales desafíos a los que se tiene que enfrentar todo terapeuta. Se trata de una tendencia a evitar realizar los cambios recomendados por el terapeuta, debido a una aprehensión o aversión al cambio (Beutler, Edwards y Someah, 2018).…”
Section: El Grado De Reactancia Con Respecto Al Cambiounclassified
“…La resistencia del paciente con respecto al cambio es uno de los principales desafíos a los que se tiene que enfrentar todo terapeuta. Se trata de una tendencia a evitar realizar los cambios recomendados por el terapeuta, debido a una aprehensión o aversión al cambio (Beutler, Edwards y Someah, 2018).…”
Section: El Grado De Reactancia Con Respecto Al Cambiounclassified
“…Indeed, the American Psychological Association Task Force on Evidence-Based Relationships and Responsiveness highlights the considerable empirical support for attending to the psychotherapy relationship and matching appropriate interpersonal approaches in conjunction with evidence-based treatments (see Norcross & Lambert, 2018;Norcross & Wompold, 2011). Relatedly, a recent metaanalysis on patients' reactance level (low versus high avoidance/resistance) suggests therapy effectiveness is associated with clinicians' corresponding level of directiveness (Beutler, Edwards, & Someah, 2018). When considering the findings of the present study concerning possible situational and/or dispositional resistance towards treatment among some veterans, maintaining an open, reflective, collaborative, and transparent therapeutic posture (as opposed to more directive and/or structured approaches) may increase engagement and/or improve therapy-related outcomes.…”
Section: Communication With Non-military Connected Personsmentioning
confidence: 99%
“…In general, people who are less open to change tend to be less compliant in treatment (Morey, 1991). A recent meta-analysis found that patients higher in resistance received less benefit from psychotherapy, and were more prone to dropping out of treatment (Beutler et al, 2018a). The same review found that patients high in resistance responded better to less directive interventions by psychotherapists, and that patients low in resistance did better in more directive therapies (Beutler et al, 2018a).…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis found that patients higher in resistance received less benefit from psychotherapy, and were more prone to dropping out of treatment (Beutler et al, 2018a). The same review found that patients high in resistance responded better to less directive interventions by psychotherapists, and that patients low in resistance did better in more directive therapies (Beutler et al, 2018a). There is no research that we are aware of that assesses those with BED on their level of resistance or interpersonal compliance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation